Pengaruh Persepsi Keamanan dan Kemanfaatan Terhadap Minat Penggunaan Kembali “Book Cabin” Melalui Kepercayaan - Sharron Tiffany Nathania; Helen Ayu Margadjie; Adrie Oktavio (Jurnal Manajerial, 2025)
Background – The rise of online check-in applications, like 'Book cabin' by Lion Air Group, highlights the need for secure and useful features to build trust and drive reuse intention. Understanding these factors is essential for enhancing user adoption and satisfaction. Aim – This research aims to analyze the influence of trust as a mediating variable of perceived security and perceived usefulness on interest in reusing Book cabin as an online check-in application at the Lion Air Group. Design / methodology / approach – The population in this research were users of the Book cabin application with a sample of 200 respondents. The sampling technique in this research is purposive sampling. Data collection was carried out by distributing questionnaires via Google Form. The data processing method in this study uses Smart-PLS which is used to test the hypothesis. Findings – The findings indicate that perceived security, perceived usefulness, and trust each have a significant positive impact on the intention to reuse the Book cabin application. Additionally, trust serves as an important mediator, strengthening the relationship between perceived security, perceived usefulness, and reuse intention. Research implication – This study contributes to the marketing fields and existing literature by examining the influence of perceived security and perceived usefulness on the intention to reuse an online check-in application. It advances previous research by exploring trust as a mediating factor, providing a deeper understanding of how trust can bridge user perceptions and behavioral intentions in digital travel services. Limitations – This study has several limitations, including the use of cross-sectional data that does not capture long-term behavioral changes and a focus on perceived security and usefulness without considering other factors like perceived ease of use, or e-WOM. Additionally, the sample is limited to users of the Book Cabin application, particularly those from the Lion Air Group. Future research should adopt a longitudinal approach, and expand the sample scope to achieve more comprehensive and generalizable findings.